A Research Paper: Providing E‐Learning Support to Part‐Time Students in Business Disciplines Using Facebook from the Multi‐Perspective, Systems‐Based (MPSB) Perspective. (16th July 2012) - Ho, Joseph Kim‐keung
<x xml:space="preserve">Abstract</x> By design, Facebook is a social networking facility. The writer, as a part‐time teacher in management subjects, adapted his Facebook account into an e‐learning facility to support his students in business studies. This paper reviews the current venture by the writer of using Facebook‐based e‐learning system to support his students. Seventeen academic forums on various management subjects have been set up to provide the learning resources to students on a virtual basis. Such forums are also intended to foster interdisciplinary and transdisciplinary learning and research by their users. The experience of this e‐learning system venture is reflected on in terms of a few contemporary systems thinking notions in general and in terms of the Multi‐perspective, Systems‐based (MPSB) thinking in particular. The MPSB research was mainly conducted in the mid‐1990 by the writer and was reported in refereed journals at that time. The present research paper provides an illustration on one of the MPSB concepts, known as 'Enlightening management education'—a concept that was least discussed in the published MPSB research. Copyright © 2012 John Wiley & Sons, Ltd.